Axiomatic districting - Clemens Puppe; Attila Tasnádi (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
In a framework with two parties, deterministic voter preferences and a type of geographical constraints, we propose a set of simple axioms and show that they jointly characterize the districting rule that maximizes the number of districts one party can win, given the distribution of individual votes (the 'optimal gerrymandering rule'). As a corollary, we obtain that no districting rule can satisfy our axioms and treat parties symmetrically.
urn:nbn:de:swb:90-229984
Keywords: D72; 330; districting; gerrymandering